The influence of credit, liquidity and non-performing loans on profttability in Commercial Banks listed on the IDX for the 2019-2022 Period - Wijaya, Anthony; Gummer, Agnes; Monica, Angel; Rosmayanti, Rosmayanti; Khairani, Rafida; Andriani, Maya (Journal of Economics and Business Letters, 2023)
This study explores the correlation among non-performing loans (NPL), credit (DER), liquidity (CR), and profitability (ROA). The data used in this investiga- tion were extracted from the Annual Published Financial Reports of 44 Commercial Banks listed on the Indonesia Stock Exchange for the period 2019–2022. The sam- ple selection involved a comprehensive approach, targeting all 44 Commercial Banks listed on the Indonesia Stock Exchange (BEI) during the years 2019 to 2022. Sta- tistical tests, specifically multiple regression methods, were applied for hypothesis testing, utilizing the F-test and T test after conducting conventional assumption tests. The findings indicate that profitability (ROA) is significantly influenced by the interplay of non-performing loans (NPL), liquidity (CR), and credit (DER). Credit (DER) has a discernible impact on profitability (ROA), whereas liquidity (CR) does not significantly affect profitability (ROA). Non-performing loans (NPL) exert a modest and unfavorable influence on profitability (ROA). The coefficient of determination (R2) for this study is 0.139, suggesting that factors beyond the scope of this research contribute to 86.1% of the variance, while variables related to credit, liquidity, and non-performing loans (NPL) can account for 13.9% of the variance in the profitability (ROA) variable.